A Comparative Study of Blood Viscosity and Fibrinogen Concentration Between Non-Pregnant Women and Parturients with Uneventful Antenatal Period - Omorogiuwa , A.; Osaikhuwuomwan, J. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Inflammation, an attendant corollary of parturition, expresses acute phase protein such as fibrinogen. Since pregnancy is contextually a hypercoagulable state, this additional expression of fibrinogen from the inflammation of parturition can be a risk for thromboembolism. This study is aimed at comparing blood viscosity and fibrinogen concentration between non-pregnant control and parturients who had an uneventful antenatal period. A total of 50 volunteers comprising 25 parturients and 25 non-pregnant control subjects from St. Philomena Catholic Hospital were studied. Informed consent from the subjects and ethical clearance from the St. Philomena catholic hospital were obtained for the study. The antenatal history was obtained from the case notes of the parturients while a pretested questionnaire was used to obtain biodata from the control subjects. The fibrinogen concentration, relative whole blood viscosity and relative plasma viscosity were measured using standard laboratory methods. Data obtained revealed that though relative whole blood viscosity and plasma viscosity were higher in parturients compared to the non-pregnant control, the difference was not statistically significant (p>0.05). However, fibrinogen concentration of the parturients (4.65±0.24g/dl) was significantly higher (p<0.05) than that of the non-pregnant control (2.19±0.13g/dl). The increase in fibrinogen concentration during the intrapartum period suggests that parturition might exacerbate the hypercoagulable state of pregnancy which is a potential risk for thromboembolism